Legal Informatics and Digital Land Governance in Indonesia and Uganda (Indonesian Journal of Agrarian Law, 2026)
Legal informatics is becoming an indispensable instrument for enhancing digital land governance through increased transparency, efficiency, and legal certainty in land administration. Nonetheless, Uganda is still facing several challenges emanating from manual land records, fraud in transactions, lack of geospatial data integration, underdeveloped technological infrastructure, and coexistence of statutory and customary land tenure systems. This paper provides a comparative analysis of the legal and institutional frameworks of digital land governance in Indonesia and Uganda, with the aim of pinpointing Uganda’s gaps in regulation and learning from Indonesia’s successful reforms in this sphere. The research applies a doctrinal legal approach entailing the comparative analysis of legislation, government policies, judicial decisions, and academic literature. The results indicate that Indonesia’s electronic land registry, One Map Policy, digital signature system, and data protection regime considerably contribute to improving land governance, while Uganda’s digitalization process is hindered by implementation difficulties and poor institutional coordination. In conclusion, it is necessary for Uganda to improve its Land Information System through geospatial database integration, electronic authentication, data protection, and recognition of customary land rights.